Consumers' perceptions of quality, packaging, and purchase intentions: an analysis of the perfume market in Oman - Khan, Zaheer Ahmed; Kamran, Hyder; Ahmed, Ishfaq; Safdar, Umar; Asim, Zeeshan; Binti Alwie, Aryaty (Sapienza: International Journal of Interdisciplinary Studies, 2025)
Local perfume brands are typically successful due to their distinct strategies and product features. The purpose of this study is to determine how packaging visual elements influence consumer purchase intentions, focusing particularly on the packaging, material, and typography of information. Furthermore, the study examines how perceived quality mediates the relationship between selected packaging elements and consumer purchase intentions. We used quantitative data collected through a field survey using structured questionnaire adapting survey items from previous studies. Total 347 respondents from Oman participated in the survey. We used the Partial Least Square Structural Equation Modelling (PLS-SEM) to analyse data. The findings revealed that packaging design and typography of information positively influence purchase intention of customers. Packaging material was found to be insignificant to influence the purchase intention. It was found that perceived quality partially mediated the relationship between independent variables (packaging design, typography) and purchase intention. In addition, there was full mediation of perceived quality in the relationship between packaging material and purchase intention. This study contributes to the literature by providing an insight into Omani consumers' attitudes regarding the aesthetics of packaging, perception of quality, and purchase intention. In the context of local market, the study suggests managers use visual elements of packaging to attract customer for increasing the likelihood of purchase. To gain a better understanding of marketing communication efforts, future research might look at the type of material as a predictor and assess the effect of gender and prices on packaging elements and purchase intention.